How Experience Quality, Prior Knowledge and Perceived Value Affect Revisit Intention to Batavia Jakarta - Maulina, Anita; Ruslan, Budiana; Ekasari, Retno (Majalah Ilmiah Bijak, 2022)
Heritage tourism at Old City of Jakarta is still far behind from the Old City in Singapore and Shanghai, so this research was conducted to see the opportunity that revisit intention to Kota tua Jakarta can be increased through the right business strategy. This study aims to determine the effect of the experience quality and prior knowledge variables on revisit intention through perceived value. Primary data was obtained from the results of 406 tourist domestic questionnaires who visited the Jakarta Old Town. Data were collected from February to March 2022.  The data is processed using SEM-PLS with SmartPLS application. By using purposive sampling method, it was concluded that the variables of experience quality and prior knowledge had a positive and significant effect.